Cultural emphasis: regionalisation as an integral component of multiculturalism within China’s contemporary education system - Kalashnyk, Lyubov; Yakushko, Nataliia; Plakhotnik, Olga; Liu, Xi; Huang, Yige (Research Journal in Advanced Humanities, 2023)
The cultural focus of this study emphasises the importance and role of culture within the process of regionalisation in the modern Chinese education system. It explores the diversity of regional cultures in China and their influence on creating a unique multicultural environment within the educational system. The article addresses the issue of regionalisation as a global trend and its specific reflection in Chinese educational theory and practice. Regionalisation, as a part of multiculturalism in China, involves recognising and integrating the diverse regional cultures within the standardised national educational framework. Methodological principles and approaches such as case studies, content analysis, qualitative data analysis, and longitudinal studies were operated. Particular attention is given to the methods employed for preserving and showcasing the cultural heritage of the regions in China, as well as their incorporation into educational programmes and events. This highlights the cultural significance of regionalisation and its relevance within the context of cultural diversity and cross-cultural exchange in modern Chinese education. China is currently intensifying efforts to promote and showcase its culture, both as a whole "Chinese culture" and "the culture of Chinese regions," emphasising the uniqueness and diversity of the ethnic groups that comprise the Chinese nation, both within the country and in the international arena.